High prevalent and incident HIV-1 and herpes simplex virus 2 infection among male migrant and non-migrant sugar farm workers in Zambia. Issue 4 (1st April 2011) - Heffron, Renee; Chao, Ann; Mwinga, Alwyn; Sinyangwe, Sylvester; Sinyama, Alex; Ginwalla, Rokaya; Shields, J Mark; Kafwembe, Emmanuel; Kaetano, Lovemore; Mulenga, Chanda; Kasongo, Webster; Mukonka, Victor; et al.
Abstract : Background: More insight is needed regarding risk factors for prevalent and incident HIV-1 infection among male farm workers in Sub-Saharan Africa to control the HIV-1 epidemic. Methods: Male farm workers were recruited from a sugar estate in Zambia to participate in a prospective cohort study. Questionnaire data were collected via interview, and testing was conducted for HIV-1, herpes simplex virus type 2 (HSV-2), and syphilis infection at baseline and follow-up between May 2006 and September 2007. Results: Among 1062 workers enrolled, HIV-1 prevalence at baseline was 20.7%. Testing HSV-2 seropositive (adjusted odds ratio (AOR) 5.4, 95% CI 3.6 to 8.1), self-reported genital ulcers in the past year (AOR 2.8, 95% CI 1.9 to 4.2), and being widowed (AOR 3.7, 95% CI 2.0 to 6.9) were significantly associated with prevalent HIV-1 infection. The HIV-1 incidence among 731 initially negative participants with at least one follow-up visit was 4.1 per 1000 person-months (95% CI 2.6 to 5.7); seroconversion was independently associated with prevalent HSV-2 infection (adjusted hazard ratio (AHR) 2.4, 95% CI 1.0 to 5.8) and incident HSV-2 infection (AHR 18.0, 95% CI 4.2 to 76.3). HIV-1 prevalence and incidence rates were similar among migrant and non-migrant workers. Conclusions: HIV-1 prevalence and incidence were high, and HSV-2 infection was a risk factor for HIV-1 acquisition. There is an urgent need to expand HIV-1 prevention programmes tailored to farm workers and their communities.